Centralized framework for elegant hospital mechanization - J.J, Jijesh; Penna, Mahaveer; Reddy Bolla, Dileep; ., Shivashankar; Palle, Satyasrikanth (International Journal of Engineering and Technology, 2019)
There is a massive demand for medical treatment and services throughout the globe which motivates to give an automated service for the people with less time delay and enhanced mechanization process. The framework is dedicated to the hospital administration at the operational level. This model is intended to screen the day by day living of the occupant, identify the possible inconveniences and mischance, corresponds with family, specialists and emergency services. Elegant hospital mechanization (EHM) framework utilizes sensor networks to provide automation in the hospital. The sensors are smaller, cheaper and intelligent connected with the communication network allowing them to monitor and control inside the hospital. This model is a measured methodology keeping in mind the end goal to successfully portray the activities and the exercises of the entire system. The system provides automation in the hospital and hence makes the individual comfortable.Â Â Â